Advanced Computer Architecture 11th Conference, ACA 2016, Weihai, China, August 22-23, 2016, Proceedings - Wu, Junjie; Li, Lian (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the 11th Annual Conference on Advanced Computer Architecture, ACA 2016, held in Weihai, China, in August 2016. The 17 revised full papers presented were carefully reviewed and selected from 89 submissions. The papers address issues such as processors and circuits; high performance computing; GPUs and accelerators; cloud and data centers; energy and reliability; intelligence computing and mobile computing.